Det landbrugsfaglige Ungdomsarbejde i Norge. Foredrag, den 11. September 1946. - Holmgren, Kåre (Tidsskrift for Landøkonomi, 2018)
Det landbrugsfaglige Ungdomsarbejde i Norge. Foredrag, den 11. September 1946.